CREATIVE BUSINESS MODELS FOR SOCIAL CHANGE: INTEGRATING TECHNOLOGY, COMMUNITY, AND SUSTAINABILITY - Arteurt Yoseph Merung; Ethan Tan; Li Wei; Johannes Muller (Journal of Social Entrepreneurship and Creative Technology, 2026)
The growing complexity of social and environmental challenges has exposed the limitations of conventional business models that prioritize economic value over societal well-being. In response, creative business models have emerged as alternative approaches that integrate technology, community engagement, and sustainability to generate social change. This study aims to examine how such creative business models are structured and how the integration of technological enablement, community participation, and sustainability principles contributes to long-term social impact. The research employs a qualitative and exploratory design based on secondary data analysis of peer-reviewed literature, policy reports, and documented case studies of social enterprises and community-based ventures. Thematic and cross-case analysis was conducted to identify recurring patterns of value creation, governance, and innovation processes. The findings reveal that social change-oriented business models are most effective when technology functions as an enabling infrastructure, communities act as co-creators rather than beneficiaries, and sustainability is embedded as a core value logic. Integrated models demonstrate greater resilience, legitimacy, and adaptability compared to fragmented approaches. The study concludes that creative business models represent a viable pathway for aligning economic activity with social and environmental objectives. Strengthening integration among technology, community, and sustainability is essential for advancing inclusive and sustainable societal transformation.